2015
DOI: 10.1002/clc.22363
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Related Mortality and In‐Hospital Complications Following ST‐Segment Elevation Myocardial Infarction: Data From a Primary Percutaneous Coronary Intervention Cohort

Abstract: Background:The increased mortality related to female gender in ST-segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PPCI) has been reported from various patient cohorts and treatment strategies with controversial results. In the present work, we evaluated the impact of female gender on mortality and in-hospital complications among a specific subset of consecutive STEMI patients managed solely by PPCI. Hypothesis: Female gender is not an independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…However, young women with AMI had an increased risk of in-hospital mortality and 1-year MACEs. Importantly, our study showed no significant gender difference in door-to-balloon time; however, young women with AMI showed a slight delay compared with men in the time between the onset of symptoms and arrival in the emergency room, which was similar to previous data for older age groups 30. These differences may be secondary to the atypical symptoms experienced by females or subject to underdiagnosis by medical staff unfamiliar with the uncharacteristic presentation of AMI among females;31 nevertheless, this is particularly disadvantageous in young women at risk of AMI.…”
Section: Discussionsupporting
confidence: 90%
“…However, young women with AMI had an increased risk of in-hospital mortality and 1-year MACEs. Importantly, our study showed no significant gender difference in door-to-balloon time; however, young women with AMI showed a slight delay compared with men in the time between the onset of symptoms and arrival in the emergency room, which was similar to previous data for older age groups 30. These differences may be secondary to the atypical symptoms experienced by females or subject to underdiagnosis by medical staff unfamiliar with the uncharacteristic presentation of AMI among females;31 nevertheless, this is particularly disadvantageous in young women at risk of AMI.…”
Section: Discussionsupporting
confidence: 90%
“…1 ). This gender differences also reflect in 30-day mortality [OR 0.64, 95% CI 0.61–0.66, P = .04, I 2 = 40%; 19 studies (n = 523,304)], [ 2 4 , 7 , 8 , 13 17 , 23 , 25 , 26 , 33 36 , 42 , 53 ] 1-year mortality [OR 0.67, 95% CI 0.60–0.75, P < .001, I 2 = 73%; 20 studies (n = 590,590)] [ 8 , 10 , 13 , 15 17 , 20 , 25 , 26 , 28 , 30 , 33 , 35 , 36 , 38 , 43 , 44 , 53 55 ] and >2-years mortality [OR 0.71, 95% CI 0.63–0.79, P = .005, I 2 = 57%; 14 studies (n = 43,096)] [ 4 6 , 18 , 19 , 23 , 29 , 31 , 34 , 36 , 40 , 43 , 52 , 56 ] (Figs. 2 – 4 ).…”
Section: Resultsmentioning
confidence: 94%
“…Studies have reported even increased mortality in females as compared to males undergoing PPCI for STEMI. 18,19 This finding is due in part to the fact that men report better QoL at baseline compared with women, and baseline QoL is a strong predictor of postrevascularization QoL. Another contributing factor is that women have more recurrent angina after PCI than men therefore persistent angina symptoms might cause lower HRQOL.…”
Section: Discussionmentioning
confidence: 99%